Challenges for the Sustainable Management of Municipal Solid Waste in Brazil. - Rizpah Besen, Gina; Fracalanza, Ana Paula (Routledge, 2016)
One of the biggest challenges for Brazilian cities is properly managing the more than 180 000 tons of municipal solid waste collected daily in the country. This article shows how this challenge is being faced in Brazil. There are legal and regulatory instruments in place, in particular the Basic Sanitation National Policy (Law no. 11.445/2007) and the Solid Waste Law (Law no. 12.305/2010). However, the targets set by the National Solid Waste Policy to put an end to dumps and dispose of waste in landfills only from June 2014 were not met. There are still dumps in over 3000 cities, which have a significant impact on environmental and public health. The universalized provision of selective collection services is present in only 20% of Brazilian cities. The large and growing market for recycling is based on the work of thousands of waste pickers, who work on the streets, live in precarious conditions, are subject to environmental hazards and put their own health at risk. Noteworthy is the selective collection model operated jointly by municipalities and waste picker organizations, formed into associations and cooperatives, and the lack of compensation for their services to industry, governments and society.
Keywords: Entsorgung; Stadt; Abfallwirtschaft; Gemeindeunternehmen; Privatwirtschaft; Abwasser; Abfallbeseitigung; Technische Infrastruktur; Metropolregion; Abfallvermeidung; Nachhaltigkeit; Müllsammlung